(untitled) (Global Journal of Management and Business Research, 2023)
The study aims to measure the role of corporate governance in reducing the negative effects of financial statements The problem of the study is to answer the following question Does corporate governance have a positive role in providing reliable financial statements Based on the statistical analysis and theoretical framework the researcher reached several results namely There is no significant relationship between the following independent variables and reducing the negative effects of the reliability of the financial statements as a dependent variable the size of the board of directors board meetings separation between the chief executive officer and the chairman of the board compliance with regulations and laws company size profitability and sector type It was also revealed that there was a positive relationship between the following independent variables and the reduction of the negative effects of the reliability of the financial statements as a dependent variable non-executive directors of the board audit quality and financial leverage The study proved that the average number of members of the Board of Directors is 9 and the average percentage of non-executive directors in the Board is about half and that the average number of Board meetings is about 5 meetings